An Empirical Study on Capital Structure Determinants of Selected ASEAN Countries - Ngo, Hoang Anh (2013)
Capital structure has been a controversial topic for decades. Conflicting arguments in theories and mixed findings in empirical work require further studies on this subject. More importantly, most previous studies have focused on developed countries and little attention is paid to emerging economies, especially ASEAN. Therefore, this study attempts to fill the gap by examining effects of capital structure's determinants on different measures of leverage of listed manufacturing companies in several ASEAN countries to see whether findings comply with the trade off theory, pecking order theory and agency theory. Eleven independent variables included are six firm-specific factors namely liquidity, tangibility, profitability, firm size, growth opportunity and non debt tax shield, together with five country-specific factors namely stock turnover ratio, domestic credit provided by banking sector as a proportion of GDP, annual GDP growth rate, inflation rate and corruption. Six dependent variables are short term leverage, long term leverage and total leverage ratios measured in both market and book value. However only market-based measures are used for analysis purpose. Book based measures are for comparison purpose with market based measures. Data are collected from 285 biggest listed manufacturing companies in Indonesia, Malaysia, Philippines, Singapore, Thailand and Vietnam during the period from 2006 to 2011. In addition, the panel data techniques is applied for analysis. In general, the results are consistent with the theories and empirical work. The study shows different influences of determinants on different debt ratios, indicating that several determinants play an important role in debt maturity choices. In addition, market based leverage measures are more appropriate than book-based leverage measures. Moreover, the six countries have relatively low debt levels as compared to developed countries. They tend to employ more short term debt than long term debt. Furthermore, regression models of all regions, except those of Malaysia, have quite high explanatory power and most determinants are vital in financing decisions. However, an exception is that the proxy for banking system development is insignificant in all models. Moreover, stock turnover ratio is also slightly related to debt ratios. Additionally, corruption almost does not affect leverage, and non debt tax shield is only significant in models of Malaysia and Vietnam. Besides, firm specific factors have more effects on capital structure than country specific factors do. Profitability and growth opportunity are dominant factors and have consistently inverse relationship with all leverage ratios. Additionally, tangibility is a major determinant, too. It is negatively correlated with short term leverage and positively correlated with long term leverage, showing both compliance and contrary with the trade off and agency theory. Liquidity does not affect long term leverage but it has a consistently significantly negative association with market based short term debt ratios of all regions. On the contrary, size substantially positively influences all market based long term debt ratios and solely has slightly positive impact on short term leverage. Macroeconomic indicators play the most vital role among country specific determinants. Annual GDP growth rate and inflation is significant in all market based leverage ratios. However the former has consistently negative sign while the latter has consistently positive sign.